2014
DOI: 10.1097/00007890-201407151-00667
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Transplant IgG Reactivity to Apoptotic Cells Correlates With Late Kidney Allograft Loss.

Abstract: Pre-existing serum antibodies have long been associated with graft loss in transplant candidates. While most studies have focused on HLA-specific antibodies, the contribution of non-HLAreactive antibodies has been largely overlooked. We have recently characterized monoclonal antibodies secreted by B cell clones derived from kidney allograft recipients with rejection that selectively bind to apoptotic cells. Here, we assessed the presence of such antibodies in pretransplant serum from 300 kidney transplant reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…These serum autoantibodies can mediate vascular injury and accelerate graft rejection 84 . However, they are present prior to transplantation and therefore are likely natural antibodies 85 . In contrast, intrarenal Bin cells expressed highly mutated IgG autoantibodies that did not bind vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…These serum autoantibodies can mediate vascular injury and accelerate graft rejection 84 . However, they are present prior to transplantation and therefore are likely natural antibodies 85 . In contrast, intrarenal Bin cells expressed highly mutated IgG autoantibodies that did not bind vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our laboratory showed that pretransplant Nabs were elevated in patients who later developed AMR. 10 In our present study, multivariable logistic regression models, depicted in Figure 2 and Figure S5 ( SDC , http://links.lww.com/TP/C651), showed that elevated pretransplant Nabs were not significantly associated with the risk of developing all AMRs (including AMR in mixed rejection profiles; OR 1.22, P = 0.4398). Pretransplant Nabs were not significantly associated with the risk of developing AMR alone (ie, excluding mixed rejection profiles; OR 1.08, P = 0.7726; not shown).…”
Section: Resultsmentioning
confidence: 42%
“…9 We have previously described Nabs in the context of kidney and heart transplantation. Elevated Nabs detected before transplantation were associated with increased graft loss after kidney transplantation 10 as well as primary graft dysfunction in heart transplant recipients. 11 Elevated Nabs were also observed in kidney transplant patients undergoing active antibody-mediated rejection (AMR).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that these autoantibodies can mediate vascular injury and accelerate graft rejection (Cardinal et al, 2013). Many of these antibodies are thought to be natural antibodies, present prior to transplantation, titers of which predict subsequent graft loss (Gao et al, 2014). In contrast, our results demonstrate that intra-renal B cells express highly mutated IgG autoantibodies which bound renal antigens.…”
Section: Discussionmentioning
confidence: 48%